Bibliometric Analysis of Artificial Intelligence in Academic Libraries - Johoran, S. Shabnam (University of Colombo, 2024)
The capability of Artificial Intelligence (AI) to identify patterns and generate predictions based on the data can be used to revolutionize the services provided by academic libraries. It is important to identify current research patterns on the use of AI in academic libraries. The study aims to map the bibliometric patterns of the research publications published in open access journals between 2019 and 2023 on the topic of AI in Academic libraries. The objectives of the study were, to identify the publications related to AI in Academic libraries from 2019 to 2023, and their citation trends, to identify the author’s contribution based on the country, to identify frequently used keywords, and to examine the authorship patterns. A bibliometric analysis was carried out on research papers on Google Scholar, Science Direct, and Taylor and Francis databases which discuss AI in academic libraries. The search was performed ...
Keywords: Artificial Intelligence; Academic Libraries; Bibliometric Analysis